The effect of murabahah, musyarakah, and transaction costs towards the profitability of Islamic commercial banks in Indonesia - Tomi Charles; Rosyeni Rasyid (Financial Management Studies, 2021)
The purpose of this study was to analyze: (1) The effect of murabahah financing on the profitability of Islamic commercial banks in Indonesia. (2) The effect of musyarakah financing on the profitability of Islamic commercial banks in Indonesia. (3) The effect of transaction costs on the profitability of Islamic commercial banks in Indonesia. The population in this study were 12 Islamic commercial banks in Indonesia. The sampling technique in this research is purposive sampling technique with a total sample of 96 samples from 2012-2019. The data used is secondary data obtained from the websites of each Islamic commercial bank in Indonesia. The result of this study indicate that: (1) Murabahah finnancing hass a positivee and significaant impact on profitabiility (ROA) of Islami commercial bank in Indonesia. (2) Musyarakah finaancing hass a negative and signifiicant efect on profitability (ROA) of Islami commercial bank ini Indonesian. (3) Transaction costs have a negative and significanteffect on profitability (ROA) of Islamic commercial banks in Indonesian. (4) Murabahahfinancing has positive and significant effect on profiitability (ROE) of Islami commerciall bank in Indonesia. (5) Musyarakah financingg has a negative and sgnificant effect on profitability (ROE) of Islami comercial bank iin Indonesian. (6) Transaction costs do not affect the profitabilityi (ROE) off Islamic commercial banks in Indonesia.